Innowacyjna przedsiębiorczość szansą rozwoju sektora MSP - Piekut, Marlena (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2010)
The purpose of this work was to introduce possibility of innovative enterprise financing in small and medium-sized enterprises. The ways of financial support have been discussed. It was pointed at the possible support in the scope of consultancy, in entrepreneurs cooperation with research and development units and assistance at elaboration and introduction on the market of new products and technologies, as well as support at providing legal protection of innovative solutions. Concrete European Union programmes supporting innovations were also indicated.